Impact of the contextual approach on the qur’anic interpretations - Syeda Asiya; Dr. Muhammad Samiullah (jihat-ul-islam, 2020)
The contextual approach, according to contextualists, is the best methodology for cognizing the true spirit and the real message of the Qur’ān, as it provides such interpretations that are based on the values of equality, fairness and justice. The contextualists assert that they seek to promote an Islam which is more humancentred, peaceful and flexible. They also regard most of the classical Qur’ānic explanations, especially pertaining to certain social issues (like the Rights of Women, Interfaith Relations and Hudūd Punishments), to be historic, specific and context-based. They argue that to determine the relevance of the Qur’ānic teachings today, such interpretations should be re-understood, re-interpreted and re-applied according to the modern context and demands. They contextualize the Qur’anic interpretations on the name of modernity, rationality, liberty, success and universality. This article aims to understand the contextual approach as well as its impact on the Qur’ānic interpretations. The thoughts and philosophy of Fazlur Rahman, the twentieth-century leading proponent of the contextual approach, are the major focus of this study. This study is an attempt to help the Muslims remove the evolving misunderstandings about Islam and stimulate them to implement the Qur’ānic wisdom in their thoughts and lives in a better way.